EKSISTENSI MASYARAKAT ADAT MORONENE DI KAWASAN TAMAN NASIONAL RAWA AOPA WATUMOHAI - Sitti Hermina; Ambo Upe (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
Moronene is one of the ethnic groups in Southeast Sulawesi. It has a culture and a variety of traditional knowledge that is used in addressing and resolving life problems, especially in order to fulfill their daily needs. This study aims to describe the existence of the Moronene Indigenous People in Rawa Aopa Watumohai National Park area. Therefore, ethnographic studies are used as a methodology to describe the complexity of the Moronene Indigenous Peoples lives in the TNRAW area which includes historical reflection, village status, demographics and kinship systems, and their socio-cultural structure. The results showed that the existence of the Moronene in Huka'ea-La'ea before the Indonesian government established the area as a conservation area even before Indonesia's independence. Moronene has long lived their lives with traditional knowledge systems, by always making nature the source of life. The existence of the Moronene Indigenous People in the TNRAW area to date is due to the existence of a system of rules for managing forests consisting of Totongano Wonua, Totongano Inalahi, Totongano Lombo, and Totongano Kadadi.